Vocal auditory-perceptual analysis in the flu-like syndrome caused by SARS-CoV-2: case series (Research, Society and Development, 2021)
The flu-like syndrome caused by the new coronavirus creates clinical manifestations of both upper and lower respiratory airways, which can impact the vocal production. Objective: To describe the vocal changes produced by the flu syndrome caused by SARS-CoV-2 during and after the cure of the disease. Methodology: Retrospective study, consisting of a convenience sample of four clinical cases (one with a clinical diagnosis and the other three with a laboratory diagnosis of COVID-19), of subjects between 56 and 81 years of age, three female and one male, in which samples of spontaneous speech were obtained through a social media application and a vocal perceptual-auditory analysis was performed. The research was approved by the ethics committee. Results: The common vocal manifestations during the infection presented lower pitch, slightly weaker loudness at the beginning of the infection, pneumophonoarticulatory incoordination, presence of breathiness, tension and fluctuation in the vocal quality, in addition to the complaint of difficulty in maintaining a pattern of respiratory normality which reflected in glottic efficiency. Conclusion: The vocal parameters were altered in the clinical cases reported with SAR-CoV-2, and health professionals must be also aware of this possibility for identification and therapeutic action so that with an increase number of samples can make possible further discussions on whether or not vocal changes can be included in the COVID-19 identification and rehabilitation protocols.